Intracompartmental Sepsis With Burn: A Case Report. (March 2016) - Chou, Chieh; Lee, Su-shin; Wang, Hui-Min; Hsieh, Tung-Ying; Lee, Hsiao-Chen; Chang, Chih-Hau; Lai, Chung-Sheng; Chang, Kao-Ping; Lin, Sin-Daw; Huang, Shu-Hung
Abstract : Abstract: Intracompartmental sepsis (IS) is a rare complication in patients with burns. Intracompartmental sepsis presents in patients with inadequate perfusion of intracompartmental tissues and subsequent ischemic necrosis and infection. Contributing factors include high-volume resuscitation, delayed escharotomies, and previous bacteremia. We describe a case of massive burns from a gas explosion and the subsequent development of IS in our intensive care burn unit. The patient presented with a 75% total body surface area burn on admission, with 39% superficial, deep partial-thickness and 26% full-thickness burns. Intracompartmental sepsis was diagnosed 45 days after admission. Anterior compartment muscles, including the tibialis anterior, extensor hallucis longus, and extensor digitorum longus, were necrotic with relatively fair nerve and vascular structures. Intracompartmental sepsis is an overwhelming, infectious complication that appears late and can occur easily in patients with major burns. Early diagnosis and management are a must for improving outcomes.